1983
DOI: 10.1090/s0002-9947-1983-0716835-6
|View full text |Cite
|
Sign up to set email alerts
|

Multi-invariant sets on tori

Abstract: Abstract. Given a compact metric group G, we are interested in those semigroups 2 of continuous endomorphisms of G, possessing the following property: The only infinite, closed, 2-invariant subset of G is G itself. Generalizing a one-dimensional result of Furstenberg, we give here a full characterization-for the case of finitedimensional tori-of those commutative semigroups with the aforementioned property.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
72
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(72 citation statements)
references
References 1 publication
0
72
0
Order By: Relevance
“…We give a brief description of the algebraic structure of irreducible Z k actions on T m , see [1,2] for more details. Irreducible Z k actions on T m .…”
Section: And a Katokmentioning
confidence: 99%
See 2 more Smart Citations
“…We give a brief description of the algebraic structure of irreducible Z k actions on T m , see [1,2] for more details. Irreducible Z k actions on T m .…”
Section: And a Katokmentioning
confidence: 99%
“…Irreducible Z k actions on T m . [1] Let α be a Z k action by automorphisms of T m . The action α is called irreducible if any non-trivial algebraic factor has finite fibres.…”
Section: And a Katokmentioning
confidence: 99%
See 1 more Smart Citation
“…Topological rigidity has been studied since the seminal paper by Furstenberg [5], in which it was shown that there is no infinite closed proper subset A ⊂ T that is invariant under multiplication by two coprime (or multiplicatively independent) integers, other than Y = T. The proper generalization for irreducible algebraic Z dactions on T m was found in [1] and generalized in [2].…”
Section: Introduction and Resultsmentioning
confidence: 99%
“…Clearly, ν (1) is the weak * limit for the sequence µ (1) k . The measures ν (1) and µ (1) k are invariant measures on the shift of finite type X 1 , and the desired second inequality follows at once, since metric entropy for a shift space is an upper semi-continuous function of the measure; see [14,Theorem 8.2].…”
Section: Lemma 31 Let Z K Be a Decreasing Chain Of α-Invariant Closmentioning
confidence: 99%